Activated antioxidant enzymes-reduced malondialdehyde concentration, and improved mineral uptake-promoted watermelon seedlings growth under boron deficiency. (5th December 2016) - Moustafa-Farag, Mohamed; Bingsheng, Fang; Malangisha Guy, Kateta; Hu, Zhongyuan; Yang, Jinghua; Zhang, Mingfang
ABSTRACT: Although boron deficiency (BD) is a drastic disorder to the agriculture crops, its effects on watermelon still unknown. Therefore, the present study investigates the effect of BD (0 and 0.5 mg L −1 ) on different morphological, physiological and biochemical traits, and mineral uptake during early seedlings stage of watermelon. B-deficiency induced leaf chlorosis in watermelon initiated from the leaf margins and tips. Despite that, BD increased shoot length, and root and shoot dry weight of BD-watermelon seedlings. BD decreased leaf chlorophyll and carotenoid contents, and photosynthetic parameters without affecting quantum yield of PSII. BD significantly inhibited total soluble protein accumulation, while leaf proline content was unaffected. A significant increase in antioxidant enzyme activities in response to higher hydrogen peroxide (H2 O2 ) generation could possibly reduced lipid peroxidation and promoted BD-watermelon plant growth. BD influenced mineral uptake variously: the induction of phosphorus (P) and zinc (Zn), and the preservation of potassium (K), calcium (Ca) and molybdenum (Mo) levels in the leaves could maintain watermelon growth; while, the inhibition of magnesium (Mg) uptake seemed to be responsible for suppressed leaf chlorophyll and photosynthesis. These results would further help in understanding the physiological pathways and mechanisms associated with BD especially in watermelon, and provide database for fertilizer recommendations in B-deficient areas.